A giant pregnancy-associated intra-abdominal desmoid tumour: not necessarily a contraindication for subsequent pregnancy - de Bree, Eelco (BioMed Central, 2013)
Desmoid tumours are rare mesenchymal tumours, often locally invasive and characteristically associated with a high local recurrence rate after resection. A potential aetiological role for female hormones is indicated. Pregnancy-associated desmoid tumours are almost exclusively located in the abdominal wall. An essential issue is how to counsel women who have had a pregnancy-associated desmoid tumour and subsequently wish to bear a child. A considerably rare case of a patient with a resection of a giant pregnancy-associated, 33 cm in diameter, intra-abdominal desmoid tumour is presented. After a subsequent pregnancy, the patient delivered healthy twins 26 months later. Fifty-four months after treatment, there are no signs of recurrent or second desmoid tumour. Although rarely located in the abdomen, pregnancy-associated desmoid tumours should be included in the differential diagnosis of intra-abdominal tumours detected during or shortly after pregnancy. Based on this case and a few others reported in the literature, subsequent pregnancy does not necessarily seem to be a risk factor for recurrent or new disease.